Effectiveness of Gargling Using Andaliman Fruit Extract (Zanthoxyllum acanthopodium) with Various Concentrations Against pH - Simah Bengi; Wardiah Wardiah; Asiah Asiah; Hafnati Rahmatan; Iswadi Iswadi (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2020)
The purpose of this study was to determine the effect of andaliman fruit extract (Zanthoxyllum acanthopodium) on salivary volume and pH. This research is an experimental study with a quantitative approach and randomized group design (RBD) design. The parameter in this research are volume and pH value of the saliva of research subjects. Data were analyzed used the Analysis of Variance test. Based on the results of the study note that the average value of salivary pH in P2 treatment (extract 10%) has the same salivary pH as the average value of salivary pH P0 + (branded mouthwash) with a pH value of 7.1 and close to the average value normal pH. From these results it was concluded that the Andaliman fruit extract solution can maintain normal salivary pH so as to maintain oral hygiene and health and be effectively used as a mouth rinse